PENGARUH LIKUIDITAS DAN HUTANG JANGKA PANJANG TERHADAP KEMAMPULABAAN (Studi Kasus pada PT. Matahari Putra Prima Tbk. dan PT. Ramayana Lestari Sentosa Tbk.) - Anwar, Yuli (STIE Binaniaga, 2011)
The purpose of this research is to get an understanding about how is liquidity and long-term debt can influence the profitabillity. By doing this research,we expect that the result can give the advantage for others related to know how the influence of liquidity and long-term debt toward the profitability. The conslusion based on the classic assumption test showing that liquidity and long-term debt has a significant influence according to profitability. These can be seen from one of the classic assumption test,test f,which means p-value from f or signification grade is 0.000 ≤ α = 5%,the result shows that H0 refused dan Ha accepted. It means there is a relation between dependent variable with various independent variable Test statistics of the variables influence liquidity and long-term debt of the ROA, a significant effect. Liquidity has a positive influence on ROA and long term-debt has a negative effect on ROA. Keywords: Liquidate,Long-term debt, and Profitability